Polypyrrole-magnetite dispersive micro-solid phase extraction for the determination of rhodamine 6G and crystal violet in textile wastewater - Kamaruddin, Amirah Farhan (2017)
Polypyrrole-magnetite (PPy-Fe3O4) dispersive micro-solid phase extraction (PPy-Fe3O4-D-μ-SPE) method combined with ultraviolet-visible (UV-Vis) spectrophotometry was developed for the determination of the selected basic dyes in textile wastewater. PPy-Fe3O4 was used as adsorbent due to its stability and excellent conductivity as well as capable of adsorbing the studied dyes. Two basic dyes, Rhodamine 6G (Rh 6G) and Crystal Violet (CV) were chosen as model compounds. Several important D-μ-SPE parameters were evaluated and optimized including sample pH, amount of adsorbent, extraction time and type of desorption solvents. The optimum PPy-Fe3O4-D-μ-SPE conditions were sample solution pH 8, 60 mg of PPy-Fe3O4 adsorbent, 5 min of extraction time and acetonitrile as the desorption solvent. Under the optimized conditions, PPy-Fe3O4-D-μ-SPE method showed good linearity in the range of 0.05-7 mg/L with coefficient of determination R2 > 0.998. The method showed good limit of detection (LOD) for the basic dyes (0.05 mg/L) and good analyte recoveries (97.4 to 111.3%) with relative standard deviations (RSD) < 10%. The developed method was successfully applied to the analysis of real textile wastewater where the concentration found was 1.03±7.9% mg/L and 1.13±4.6% mg/L for Rh 6G and CV respectively. From the result, it can be concluded that PPy-Fe3O4-D-μ-SPE method can be adopted for the extraction and analysis of trace level basic dyes in short time (total analysis time < 15 min).